Konstruksi Frasa Idiomatik dalam Novel Orang-Orang Biasa Karya Andrea Hirata - Prasetyo, Dika Rama; Haryadi (UIR PRESS, 2023)
This study applies a theoretical approach to phraseological syntax, as well as a qualitative descriptive methodological approach. Methods and techniques of data collection using the listening method combined with basic tapping techniques and advanced techniques in the form of note taking techniques. The method of data analysis is the distribution method with the direct element division technique (BUL) and the advanced technique in the form of the dissipation technique. Methods of presenting the results of the analysis in the form of informal methods and formal methods. This study obtained the results in the form of 10 forms of idiomatic phrases collected from Andrea's Ordinary People novel, namely the phrases stick your nose, subordinates, golden child of justice, blind pay, street vendors, raise your hands, open your mouth, wash money, go out of business, and cold-blooded. The patterns of idiomatic phrase formation consist of patterns of Noun+Noun (N+N), Noun+Noun+Noun (N+N+N), Noun+Adjective (N+Adj), Noun+Numeralia (N+Num), Verbs+Nouns (V+N), and Verbs+Adjectives (V+Adj). It is hoped that this research can add insight into the forms and patterns of idiomatic phrase formation in Andrea Hirata's Ordinary People novel as well as become a reference source for further research on similar topics.